The Mediating Effect of Organizational Productivity on The Relationship between Competencies, Engagement, And Commitment with Talent Management & Succession Planning Programs in Saudi Arabia - Kharroub N.; Isa A.A.B.M.; Islam M.K. (World Scientific and Engineering Academy and Society, 2025)
The purpose of the current study is to investigate the relationship between Competencies, Engagement, and Commitment with the Talent Management and Succession Planning Programs in the Saudi Electricity Company. In addition, the mediating role of the Organizational Productivity on the relationship between the variables. This study was conducted following the quantitative research methods through the distribution of 408 questionnaires to the employees of the Saudi Electricity Company. The results revealed that significant relationship between Competencies, Engagement, and Organizational Productivity with the success of the Talent Management & Succession Planning programs, which support what was found in the majority of the previous published literature. But unlike most of the published literature, Commitment was found to be insignificant to the success of the Talent Management & Succession Planning programs. In addition, this study showed that Organizational Productivity played a significant mediating effect on the relationship between Engagement and Commitment with Talent Management & Succession Planning programs. However, Organizational Productivity has shown an insignificant mediating effect on the relationship between Competencies and Talent Management & Succession Planning programs. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.